Randomised controlled monocentric trial to compare the impact of using professional actors or peers for communication training in a competency-based inverted biochemistry classroom in preclinical medical education - Schneider, Achim; Messerer, David Alexander Christian; Kühn, Veronika; Horneffer, Astrid; Bugaj, Till Johannes; Nikendei, Christoph; Kühl, Michael; Kühl, Susanne Julia (BMJ open, 2022)
Objective In medical education, biochemistry topics are usually knowledge based, and students often are unaware of their clinical relevance. To improve students’ awareness of the relevance, we integrated communication skills training into biochemistry education. No studies before have examined the difference between peer and standardised patient (SP) role plays where students explain the biochemical background of a disease in patient-centred language. Therefore, we evaluated whether students’ self-perceived competency in Canadian Medical Education Directives for Specialists (CanMEDS) roles and their opinion of the quality of role play differ if the layperson is played by peers or SPs. - Methods We randomly assigned medical students in a preclinical semester to one of the two groups. The groups used predefined scripts to role play a physician-parent consultation with either a peer (peer group) or an SP (SP group) in the parent role. Students then assessed the activity’s effects on their competency in CanMEDS roles and motivation and the relevance of the role play. To determine whether students achieved biochemistry learning goals, we evaluated results of a biochemistry exam. - Results Students’ self-perceived competency improved in both groups. The SP group rated their competency in the roles ‘Scholar’ and ‘Professional’ significantly higher than the peer group did. The peer group rated their competency in the role of ‘Medical Expert’ significantly higher if they played the role of the parent rather than physician or observer. The SP group agreed more that they were motivated by the role play and wanted to receive more role play-based teaching. The SP group perceived the role play as being realistic and rated the feedback discussion as more beneficial. The examination results were the same in both groups. - Conclusion We showed that role plays in a biochemistry seminar improve students’ self-perceived competency. The use of SPs has some advantages, such as being more realistic.
First published May 26, 2022
Gesehen am 04.07.2022